x → 0 + lim 2 0 1 6 cos ( 2 0 1 6 x ) − cos 2 0 1 6 ( 2 0 1 6 x ) ( cos ( x ) cos ( 2 x ) 3 cos ( 3 x ) ⋯ 2 0 1 6 cos ( 2 0 1 6 x ) − cos ( x ) cos 2 ( 2 x ) cos 3 ( 3 x ) ⋯ cos 2 0 1 6 ( 2 0 1 6 x ) )
The limit above has a closed form. Find the value of this closed form.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We use Approximation Mclaurin Series we know that mclaurin series for cos ( x ) = n = 0 ∑ ∞ ( − 1 ) n ( 2 n ) ! x 2 n = 1 − 2 ! x 2 + 4 ! x 4 − 6 ! x 6 + ⋯
and too this problem we only need the first of 2 term. So cos ( x ) ≈ 1 − 2 ! x 2 = 1 − 2 x 2
then limit become , x → 0 + lim ( 1 − 2 2 0 1 6 2 x 2 ) 2 0 1 6 1 − ( 1 − 2 2 0 1 6 x 2 ) 2 0 1 6 ( 1 − 2 x 2 ) ( 1 − 2 4 x 2 ) 2 1 ( 1 − 2 9 x 2 ) 3 1 ⋯ ( 1 − 2 2 0 1 6 2 x 2 ) 2 0 1 6 1 − ( 1 − 2 x 2 ) ( 1 − 2 4 x 2 ) 2 ( 1 − 2 9 x 2 ) 3 ⋯ ( 1 − 2 2 0 1 6 x 2 ) 2 0 1 6 After that, we use Approximation Binomial Newton from that we know ( 1 + x ) n = k = 0 ∑ n ( k n ) x k
then the approximation is we take first 2 term ( 1 + x ) n ≈ ( 0 n ) + ( 1 n ) x 1 = 1 + n x
Now See a denominator become : ( 1 − 2 2 0 1 6 x 2 ) 2 0 1 6 1 − ( 1 − 2 2 0 1 6 x 2 ) 2 0 1 6 = ( 1 − 2 2 0 1 6 x 2 ) − ( 1 − 2 2 0 1 6 3 x 2 ) = 2 2 0 1 6 3 − 2 0 1 6 x 2 = 2 1 ( 2 0 1 6 ) ( 2 0 1 6 2 − 1 ) x 2
so the limit become x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 6 2 − 1 ) x 2 ( 1 − 2 1 x 2 ) ( 1 − 2 2 x 2 ) ( 1 − 2 3 x 2 ) ⋯ ( 1 − 2 2 0 1 6 x 2 ) − ( 1 − 2 1 3 x 2 ) ( 1 − 2 2 3 x 2 ) ( 1 − 2 3 3 x 2 ) ⋯ ( 1 − 2 2 0 1 6 3 x 2 ) = x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 6 2 − 1 ) x 2 ( 1 − 2 1 ( 1 + 2 + 3 + ⋯ + 2 0 1 6 ) x 2 + ( 1 × 2 + 1 × 3 + ⋯ + 2 0 1 5 × 2 0 1 6 ) x 4 + ⋯ ) − ( 1 − 2 1 ( 1 3 + 2 3 + 3 3 + ⋯ + 2 0 1 6 3 ) x 2 + ( 1 3 2 3 + 1 3 3 3 + ⋯ + 2 0 1 5 3 2 0 1 6 3 ) x 4 + ⋯ ) = x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) x 2 ( 1 − 2 1 ( 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) x 2 + ( 1 × 2 + 1 × 3 + ⋯ + 2 0 1 5 × 2 0 1 6 ) x 4 + ⋯ + ( ⋯ ) x 4 0 3 2 ) − ( 1 − 2 1 ( ( 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) 2 ) x 2 + 4 1 ( 1 3 2 3 + 1 3 3 3 + ⋯ + 2 0 1 5 3 2 0 1 6 3 ) x 4 + ⋯ + ( ⋯ ) x 4 0 3 2 ) = x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) x 2 ( 2 1 ( ( 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) 2 − 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) x 2 + 4 1 ( 1 × 2 + 1 × 3 + ⋯ + 2 0 1 5 × 2 0 1 6 − 1 3 2 3 + 1 3 3 3 + ⋯ + 2 0 1 5 3 2 0 1 6 3 ) x 4 + ⋯ + ( ⋯ ) x 4 0 3 2 ) x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) x 2 ( 2 1 ( ( 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) 2 − 2 1 ( 2 0 1 5 ) ( 2 0 1 6 ) ) x 2 + 4 1 ( 1 × 2 + 1 × 3 + ⋯ + 2 0 1 5 × 2 0 1 6 − 1 3 2 3 + 1 3 3 3 + ⋯ + 2 0 1 5 3 2 0 1 6 3 ) x 4 + ⋯ + ( ⋯ ) x 4 0 3 2 )
divide by x 2 for denominator and numerator. We have x → 0 + lim 2 1 ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) ( 2 1 ( ( 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) ) 2 − 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) ) + 4 1 ( 1 × 2 + 1 × 3 + ⋯ + 2 0 1 5 × 2 0 1 6 − 1 3 2 3 + 1 3 3 3 + ⋯ + 2 0 1 5 3 2 0 1 6 3 ) x 2 + ⋯ + ( ⋯ ) x 4 0 3 0 ) subtitute for limit x → 0 + then the answer is
2 1 ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) ( 2 1 ( ( 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) ) 2 − 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) ) ) = ( 2 0 1 6 ) ( 2 0 1 5 ) ( 2 0 1 7 ) ( 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) ) ( 2 1 ( 2 0 1 6 ) ( 2 0 1 7 ) − 1 ) = 4 1 2 0 1 5 2 0 1 6 × 2 0 1 7 − 2 = 4 1 2 0 1 5 ( 2 0 1 5 + 1 ) ( 2 0 1 5 + 2 ) − 2 = 4 1 2 0 1 5 2 0 1 5 2 + 3 × 2 0 1 5 = 4 2 0 1 5 + 3 = 4 2 0 1 8 = 5 0 4 . 5
Problem Loading...
Note Loading...
Set Loading...
Considering the first couple of terms in the relevant Taylor series, we have ( cos j x ) j 1 ≈ 1 − 2 1 j x 2 + ⋯ ( cos j x ) j ≈ 1 − 2 1 j 3 x 2 + ⋯ and hence j = 1 ∏ n ( cos j x ) j 1 j = 1 ∏ n ( cos j x ) ) j ≈ 1 − 2 1 j = 1 ∑ n j x 2 + ⋯ = 1 − 4 1 n ( n + 1 ) x 2 + ⋯ ≈ 1 − 2 1 j = 1 ∑ n j 3 x 2 = 1 − 8 1 n 2 ( n + 1 ) 2 x 2 + ⋯ and hence j = 1 ∏ n ( cos j x ) j 1 − j = 1 ∏ n ( cos j x ) ) j ≈ [ 8 1 n 2 ( n + 1 ) 2 − 4 1 n ( n + 1 ) ] x 2 + ⋯ = 8 1 n ( n + 1 ) ( n − 1 ) ( n + 2 ) x 2 + ⋯ while ( cos n x ) n 1 − ( cos n x ) n ≈ 2 1 ( n 3 − n ) x 2 + ⋯ = 2 1 n ( n − 1 ) ( n + 1 ) x 2 + ⋯ and hence ( cos n x ) n 1 − ( cos n x ) n ∏ j = 1 n ( cos j x ) j 1 − ∏ j = 1 n ( cos j x ) ) j ≈ 4 1 ( n + 2 ) + ⋯ and hence this ratio tends to 2 1 ( n + 2 ) as x → 0 + . With n = 2 0 1 6 , the answer is 5 0 4 . 5 .